2012
DOI: 10.1111/j.1346-8138.2012.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Two patterns of solar lentigines: A histopathological analysis of 40 Japanese women

Abstract: Solar lentigines are common acquired pigmented lesions on sun-exposed skin. Their histopathological features have been reported as large numbers of melanocytes at the base of clubbed and budding rete ridges. In this study, biopsies were taken from facial solar lentigines in 40 Japanese women, and the sections were stained using hematoxylin-eosin, Fontana-Masson, and immunostained for melanocytes and Langerhans cells in order to verify the histological patterns of Japanese patients. We characterized the histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Nonetheless, flattened rete ridges are a frequent finding in SL, and tend to occur more often on the face compared with other anatomical sites. In an earlier report, more than half of cases of facial SL showed flattening rather than elongation of rete ridges. In a more recent study carried out in Japanese patients, more severe solar elastosis and fewer Langerhans cells were seen in the epidermis in the 20 cases (out of 40) that showed flattened rete ridges, compared with the budding (elongated) group .…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Nonetheless, flattened rete ridges are a frequent finding in SL, and tend to occur more often on the face compared with other anatomical sites. In an earlier report, more than half of cases of facial SL showed flattening rather than elongation of rete ridges. In a more recent study carried out in Japanese patients, more severe solar elastosis and fewer Langerhans cells were seen in the epidermis in the 20 cases (out of 40) that showed flattened rete ridges, compared with the budding (elongated) group .…”
Section: Introductionmentioning
confidence: 80%
“…In an earlier report, more than half of cases of facial SL showed flattening rather than elongation of rete ridges. In a more recent study carried out in Japanese patients, more severe solar elastosis and fewer Langerhans cells were seen in the epidermis in the 20 cases (out of 40) that showed flattened rete ridges, compared with the budding (elongated) group . The authors suggested that more severely sun‐damaged solar lentigines might show the changes observed in the flattened rete ridge group.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The lentigines have been widely investigated histologically, the main characteristics being epidermal hyperplasia, a budding of the rete ridges, and hyperpigmentation …”
Section: Introductionmentioning
confidence: 99%